Ranger Pink: Perempuan Pekerja Tambang di Antara Dua Dunia - Tini - Suryaningsi (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2017)
Ranger pink is the term used to refer to women who works to operate dump truck in mining area of Sorowako. Despite the fact that operating dump truck is a hardwork since it operates a big equipment in open space area and sometimes in a night shift, women get involved in such kind of work, and called ranger pink. This article aims to explore how ranger pink manage to live their two completely different world, at work and at home. It was discovered that recruitment process, working activities, as well as working shift are genderless. However, the company has specific policy in regard to women which deal with their reproductive health and facilities for ranger pink who are in the night shift work. Working as ranger pink has given significant change in their life. The family pays more attention to ranger pink, they get involved in the decision making in the family, they can help the family economically, and increase social status of the family. Ranger pink try to balance between her work and her domestic activites with the help of the husband and/or other members of the family. In spite of the fact that ranger pink are welcome by their male dump truck operator, they are also criticised in participating in such work, and suggesting to have other ‘normal work’ for women. Ranger pink are also criticised by the surrounding community because of their participation in such kind of work, especially because their best place is at home to take care of their children. Therefore, women are to be blamed when something happen to children.